The study of Waste Management practices within households in Khakhanwa Village, Thulamela Municipality - Mabadahanye, Vhonani (My University, 2017)
The sanitary state of an area is largely influenced by waste handling practices of the residents and measures in place for safe waste evacuation and disposal. Despite strategies that the municipality and local communities have put in place; namely, collection of wastes in one central spot in some villages, littering of all types of wastes is still on the increase in many rural areas. The focus of this study was on common refuse generated at Khakhanwa Village, different waste management practices and the knowledge of villagers on the impact of poor refuse management. The study was carried out using the quantitative, descriptive methodology. A total population of 312 households participated. Data was collected using a structured questionnaire and ethical aspects were taken into consideration. Data was analysed descriptively using SPSS version 22.0. It is presented using graphs, tables and pie chart. The findings show that the respondents satisfactorily showed understanding of waste management and the impact of poor waste management. Due to lack of waste services, the majority of the residents resort to storing wastes within their homes, burning it and disposing of it in open dumping sites as major waste management practices. The most familiar wastes in Khakhanwa village are decomposable wastes, napkins and plastics. These findings call for strengthened waste services in rural areas and more waste education amongst all villagers. Policies on waste management need to be put in motion. Communities need to be equipped with the knowledge of reducing, reusing and recycling for the purpose of limiting wastes. Finally school curricula should be adjusted such that they inform learners about waste management from early ages.
MPH
Department of Public Health
Keywords: Waste management; UCTD; Waste disposal; Practices; Household waste; 363.7280968257; Refuse and refuse disposal -- South Africa -- Limpopo; Hazardous wastes -- South Africa -- Limpopo; Waste products -- South Africa -- Limpopo; Households -- South Africa -- Limpopo